2022
DOI: 10.1037/adb0000741
|View full text |Cite
|
Sign up to set email alerts
|

Affect and subjective cognitive functioning by depression symptom levels during naturalistic cigarette smoking in premenopausal females who smoke daily.

Abstract: Objective: High negative affect, low positive affect, and low cognitive functioning are depression-related states that may be particularly relevant to females who smoke cigarettes and may be more prominent following overnight tobacco abstinence. This study aimed to assess relations between depression symptom levels and negative affect, positive affect, and subjective cognitive functioning in premenopausal females who smoke. Methods: Premenopausal females who smoke daily with low (n = 66) or elevated (n = 33) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The demographic characteristics of the participants are described in Table 1. The median age of the participants was 55(48,62), and before adjustment, the Non-IA group was 57 (49,63) and the IA group was 54 (47,61), with a statistically different age between the two groups.…”
Section: Baseline Characteristics Of the Participantsmentioning
confidence: 94%
See 1 more Smart Citation
“…The demographic characteristics of the participants are described in Table 1. The median age of the participants was 55(48,62), and before adjustment, the Non-IA group was 57 (49,63) and the IA group was 54 (47,61), with a statistically different age between the two groups.…”
Section: Baseline Characteristics Of the Participantsmentioning
confidence: 94%
“…Many previous studies have shown that women's choice of induced abortion is related to age, BMI, annual household income, smoking status, drinking frequency, and other factors [44][45][46][47][48][49][50][51][52][53] . Our study was found in the BMI < 25, kg/m2 subgroup, The difference in correlation between induced abortion and BDMD was not signi cant.…”
Section: Page 9/16mentioning
confidence: 99%
“…Items are summed to determine a total score ranging from 0 to 60. As in our prior work (Pang, Tucker, D'Orazio, Weinberger, & Guillot, 2022;Tucker, et al, 2022), a binary CESD score was created for elevated depression symptoms (≥20) and low depression symptoms (<20). A meta-analysis in general populations and primary care settings found a cutoff of 20 showed better sensitivity to specificity trade-off than the generally recommended cutoff of 16 (Vilagut, Forero, Barbaglia, & Alonso, 2016).…”
Section: The Center For Epidemiologic Studies Depression Scale (Ces-d)mentioning
confidence: 99%